2021
DOI: 10.1371/journal.pone.0255064
|View full text |Cite
|
Sign up to set email alerts
|

Superior pedal function recovery of newly designed three spike insole over total contact insole in refractory plantar fasciitis: A randomized, double-blinded, non-inferiority study

Abstract: Introduction Plantar fasciitis is one of the common foot complaints that is chronic and can induce dysfunction. Total contact insole (TCI) is simple but effective in treating plantar fasciitis. Despite its effect, the cost and long duration for production have been the major flaws. Therefore, we developed a newly designed three-spike insole (TSI) that can be commercially productive and compared its clinical outcomes to TCI. Methods Patients with plantar fasciitis refractory to conservative treatment for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These results will be employed to compare with laboratory-made insoles where the effects of the PCM, epoxy resin, and thickener on the samples will be evaluated. Hardness results were consistent with other results found in the literature [ 25 , 26 ] so manufactured insoles could be employed for further analyses.…”
Section: Resultssupporting
confidence: 89%
“…These results will be employed to compare with laboratory-made insoles where the effects of the PCM, epoxy resin, and thickener on the samples will be evaluated. Hardness results were consistent with other results found in the literature [ 25 , 26 ] so manufactured insoles could be employed for further analyses.…”
Section: Resultssupporting
confidence: 89%
“…ABAQUS was then used for contact pressure analysis, revealing a 25% reduction in maximum plantar pressure compared to the flat insole. Studies indicate that total contact insoles offer more benefits to diabetic foot than flat insoles ( Ahmed et al, 2020 ; Shim et al, 2021 ). El-Hilaly et al (2013) found the efficacy of total contact insoles in offloading foot pressures in diabetic patients following partial first-ray amputations, leading to significant pressure reduction compared to flat insoles during standing and walking.…”
Section: Design Of Diabetic Foot Insolesmentioning
confidence: 99%